Web Based Archives Storage System at Perumda Air Minum Tirto Negoro Sragen: Sistem Penyimpanan Arsip Berbasis Web di Perumda Air Minum Tirto Negoro Sragen - Anjarwati, Daristiyana Puput; Pantjarani, Ari; Hastomo, Mursid Dwi (Politeknik Harapan Bangsa Surakarta, 2023)
PERUMDA Tirto Negoro Drinking Water, Sragen Regency is one of the regional-owned business units engaged in the distribution of clean water for the community in Sragen. PERUMDA Tirto Negoro Drinking Water Sragen has many parts in its business process. This makes many important documents that must be stored and sometimes makes searching for a document a problem because you have to search first in the archive ledger that is recorded manually. Information systems in a government or private agency are needed in order to make the performance of an agency run well. Therefore, it is important to create a web-based system for archive storage so that the search is more effective and does not take too long. This web-based system application uses PHP programming methods and web-based codeIgniter as well as MySQL as database storage. The result of this design is a web-based archive information system that can manage input for recording letters, searching for letters, and storing archives digitally.